Methadone is a Non‐Competitive Antagonist at the α4β2 and α3* Nicotinic Acetylcholine Receptors and an Agonist at the α7 Nicotinic Acetylcholine Receptor. (7th October 2014) - Talka, Reeta; Salminen, Outi; Tuominen, Raimo K.
Abstract Nicotine–methadone interactions have been studied in human beings and in various experimental settings regarding addiction, reward and pain. Most methadone maintenance treatment patients are smokers, and methadone administration has been shown to increase cigarette smoking. Previous in vitro studies have shown that methadone is a non‐competitive antagonist at rat α3β4 nicotinic acetylcholine receptors (nAChR) and an agonist at human α7 nAChRs. In this study, we used cell lines expressing human α4β2, α7 and α3* nAChRs to compare the interactions of methadone at the various human nAChRs under the same experimental conditions. A [3H]epibatidine displacement assay was used to determine whether methadone binds to the nicotinic receptors, and 86Rb+ efflux and changes in intracellular calcium [Ca2+]i were used to assess changes in the functional activity of the receptors. Methadone displaced [3H]epibatidine from nicotinic agonist‐binding sites in SH‐EP1‐hα7 and SH‐SY5Y cells, but not in SH‐EP1‐hα4β2 cells. The Ki values for methadone were 6.3 μM in SH‐EP1‐hα7 cells and 19.4 μM and 1008 μM in SH‐SY5Y cells. Methadone increased [Ca2+]i in all cell lines in a concentration‐dependent manner, and in SH‐EP1‐hα7 cells, the effect was more pronounced than the effect of nicotine treatment. In SH‐EP1‐hα4β2 cells, the effect of methadone was negligible compared to that of nicotine. Methadone pre‐treatment abolished the nicotine‐induced response in [Ca2+]i in all cell lines expressing nAChRs. In SH‐EP1‐hα4β2 and SH‐SY5Y cells, methadone had no effect on the 86Rb+ efflux, but it antagonized the nicotine‐induced 86Rb+ ion efflux in a non‐competitive manner. These results suggest that methadone is an agonist at human α7 nAChRs and a non‐competitive antagonist at human α4β2 and α3* nAChRs. This study adds further support to the previous findings that opioids interact with nAChRs, which may underlie their frequent co‐administration in human beings and might be of interest to the field of drug discovery.